Humanise corporate governors – eradicating accounting fraud by augmenting ethical sensitivity and religiosity in accounting education - Jaspal, S. J. S. *; Mustafa, M. H.; Kamaljeet, K. (Universiti Malaysia Pahang, 2018)
This paper reviews behavioural accounting and the relationship between ethical sensitivity and religiosity to influence the behaviour of accountants when faced with ethical dilemmas. Accounting fraud is on the rise and alternative measures must be looked into to restraint this issue. Rather than focusing only on greater transparency and more stringent control through improving and introducing new rules and regulations, ethical reasoning should also be addressed seriously, with emphasis on ethical sensitivity and religiosity to assist individuals to justify their actions. This study finds that accounting ethics education intervention at tertiary level may be the solution. Future accounting practitioners should be exposed to ethical dilemmas as part of the curriculum to handle ethical issues appropriately. Establishing the link between ethical sensitivity and religiosity and applying effective accounting ethics teaching methods at tertiary level to inculcate ethical sensitivity via religiosity will solve unethical accounting practices. There is a need for institutes of higher learning and the Ministry of Education to induce the appreciation of relevant religious tenets related to look into this issue.